From the bush to the bench: the annual Nothobranchius fishes as a new model system in biology - Cellerino, Alessandro; Valenzano, Dario R; Reichard, Martin (Biological reviews of the Cambridge Philosophical Society, 2016)
African annual fishes from the genus Nothobranchius are small teleosts that inhabit temporary water bodies subject to annual desiccation due to the alternation of the monsoon seasons. Given their unique biology, these fish have emerged as a model taxon in several biological disciplines. Their increasing popularity stems from the extremely short lifespan that is the result of their specific life-history adaptations and is retained under laboratory conditions. Nothobranchius furzeri, the most popular laboratory species, is the vertebrate species with the shortest lifespan recorded in captivity. In the laboratory, adults of different Nothobranchius species and populations live between 3 and 18 months and, notably, there is a negative correlation between the captive lifespan of a species and the aridity of their habitat. Their short lifespan is coupled to rapid age-dependent functional decline and expression of cellular and molecular changes comparable to those observed in other vertebrates, including humans. The recent development of transgenesis in this species makes it possible to insert specific constructs into their genome, and the establishment of transgenic lines is facilitated by their very rapid generation time, which can be as short as 1 month. This makes Nothobranchius species particularly suited for investigating biological and molecular aspects of ageing and ageing-associated dysfunctions. At the same time, they also represent a unique model taxon to investigate the evolution of life-history adaptations and their genetic architecture. We review their natural history, including phylogenetic relationships, distribution in relation to habitat conditions and natural selection for differential longevity, population structure and demography, and life cycle with emphasis on diapause that may occur at three stages during embryonic development. We further critically evaluate their use as a laboratory model for understanding the evolution of a rapid ageing rate and its consequences for other life-history traits, for cellular, molecular and integrative traits associated with the ageing process, high incidence of neoplasias, their utility for genome-wide gene-expression studies, and as a model for quantitative genetics. We summarize recent achievements in fostering Nothobranchius species as a widely applicable model system, including an annotated transcriptome, successful transgenesis, and existence of viable inbred lines. We compare the conditions they experience in the wild and in captivity and suggest that they are an ideal taxon to investigate natural genetic variation in a laboratory setting. We conclude that Nothobranchius species - and N. furzeri in particular - could become a unique model taxon that bridges interests in ecological and biomedical research. We hope that a conceptual and methodological integration of these two branches of biology will provide important new insights.
Keywords: Cyprinodontiformes; ageing; regulace genové exprese; inbred lines; geneticky modifikovaná zvířata; diapause; model species; stárnutí; modely u zvířat; zvířata; senescence; Aging; annual fish; Animals, Genetically Modified; killifish; Gene Expression Regulation; longevity; life-history traits; quantitative genetics; Models, Animal; Animals